Mechanical Terahertz Modulation Based on Single‐Layered Graphene. Issue 7 (7th February 2018) - Cheng, Long; Jin, Zuanming; Ma, Zongwei; Su, Fuhai; Zhao, Yang; Zhang, Yongzhuan; Su, Tongyu; Sun, Yan; Xu, Xueli; Meng, Zhi; Bian, Yuecheng; Sheng, Zhigao
Abstract: The 2D terahertz (THz) modulator, enabling efficient manipulation of such versatile band in nanoscale, is crucial for THz microdevices and systems, but its implementation is difficult and remains challenging in practice. Here, a novel 2D THz modulator based on single‐layered graphene under mechanical strain is demonstrated. Bidirectional, i.e., both positive and negative, THz modulation effect is realized by utilizing unconventionally distributed strains on graphene. Such mechanical modulation is found to be stable and reversible, and its modulation depth can exceed 26% at 1 THz under 10 –2 GPa strain. Observations of both the strain and frequency dependent modulation behavior evidence the mechanical strain‐induced change of the Dirac‐like energy dispersion in graphene, which is distinctive from that of the electrical and optical approaches. Due to the reliability and wide applicability of mechanical forces, these results provide an alternative route for chip‐scale THz modulation devices based on 2D materials. Abstract : A bidirectional terahertz modulator is realized by exerting mechanical strain on single‐layered graphene. The modulation depth is frequency dependent and could reach 26% in 1 THz with 1% mechanical deformation applied. This modulator could be used in signal modulation and strain sensing devices.